2015
DOI: 10.26417/ejes.v2i1.p136-143
|View full text |Cite
|
Sign up to set email alerts
|

Customer Relationship Management (CRM) in Banking Sector in Albania

Abstract: The aim of this paper is to examine the Customer Relationship Management as a new methodology looks forward to identify and attract consumers through the process of developing relationships (business -customer). The methodology of the CRM aims to maintain customer satisfaction and increase consumer loyalty. The purpose of this paper is to know the basic capabilities of CRM systems and in-depth knowledge of methods and management techniques customer relationships. This paper will examine the methods and techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…This indicates that there is a significant relationship between CRM practices and customer retention. This revelation from the study is consistent with several studies, such as San and Hardjono (2017), Abbas et al (2017), Bashir (2017), Hettiarachchy andSamarasinghe (2016), andRamaj (2015), which also found that CRM and its practices had a positive and a significant impact on customer retention. This further suggests that banks' attempts to improve their CRM practices will help them retain customers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that there is a significant relationship between CRM practices and customer retention. This revelation from the study is consistent with several studies, such as San and Hardjono (2017), Abbas et al (2017), Bashir (2017), Hettiarachchy andSamarasinghe (2016), andRamaj (2015), which also found that CRM and its practices had a positive and a significant impact on customer retention. This further suggests that banks' attempts to improve their CRM practices will help them retain customers.…”
Section: Discussionsupporting
confidence: 92%
“…Duwailah and Hashem (2019) verified that the utilization of customer knowledge management enables businesses to increase its profitability through CRM practices. According to San and Hardjono (2017), customer retention is significantly linked with variables such as customer orientation and knowledge management, Moreover, other researchers Radaideh and Al-Talafih (2017) and Ramaj (2015) indicated clearly that technology-based CRM also improves satisfaction of customers. Through their study, Abbas et al (2017) verified that firms should focus on the performance factors for building a successful CRM in order to have a strong connection with the consumers, which enhances the attitude toward customer retention.…”
Section: Literature Reviewmentioning
confidence: 99%